KEMAMPUAN GURU DALAM MELAKSANAKAN PAKEM DI SEKOLAH DASAR - Maratun Nafiah; Gusti Yarmi; Dudung Amir S. (Perspektif Ilmu Pendidikan, 2008)
The student centered learning is the learning method that activates the students and could be carried out by applying active, creative, effective, and joyfull learning (PAKEM). This qualitative research aims of findings out PAKEM is in implemented at four elementary schools in Bali and Central Java provinces. The research was carried out from February to October 2007, concludes: (1) a lot of conventional approach (teacher-centered) are still practical in the classroom; (2) the classroom situations doesn’t reflect any active, creative, effective, joyfull learning (PAKEM) characteristics; (3) none of student’s work show up on the classroom wall; (4) the classroom is not fully explored to be a learning resource; and (5) instructional methods use are dominated by the teacher. In addition it is also important to know that the learning process doesn’t take benefit of the existing facilities with in this situation, the group study, self study, and the problem based learning are not practised optimally neither the use of classs paces as the source of learning. More over, the methods being used were toll the one way instructional mode. It was also important to be mentioned that there were no usage of the sourrounding atmosphere as the leasy source. The optimalization of the group study, self study and the problem based learning hadn’t been achieved yet.